High-temperature-ablation-resistant (Hf-Zr-Ti-Ta) C carbide superhigh-temperature ceramic and preparation method thereof

The (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high temperature ceramics prepared by carbothermal reduction and pressureless sintering methods have solved the problem of insufficient ablation resistance of single-component ceramics in high-temperature oxygen flow erosion environments, realizing efficient and low-cost mass production, and are suitable for thermal protection of aerospace hot-end components.

CN120943642APending Publication Date: 2025-11-14HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510998226.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing single-component ultra-high temperature ceramics have insufficient resistance to ablation in ultra-high speed, ultra-high temperature oxygen-containing flow erosion environments. Traditional sintering processes are costly and energy-intensive, making them unsuitable for mass production.

Method used

(Hf-Zr-Ti-Ta)C quaternary carbide ultra-high temperature ceramics were prepared by carbothermal reduction and pressureless sintering. By simplifying the sintering process, the cost was reduced, and ceramic materials with excellent ablation resistance were prepared.

Benefits of technology

After being ablated for 30 seconds under an oxyacetylene flame at 3000℃, the ceramic structure remained intact, the oxide layer was dense, and the ablation resistance was significantly improved, making it suitable for thermal protection of aerospace hot-end components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943642A_ABST
    Figure CN120943642A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ultrahigh-temperature ceramic materials, and discloses high-temperature-ablation-resistant (Hf-Zr-Ti-Ta) C carbide ultrahigh-temperature ceramic and a preparation method thereof. The preparation method comprises the following steps: firstly, mixing HfO2, ZrO2, TiO2, Ta2O5 and C powder, then carrying out heat treatment in a high-temperature heat treatment furnace, and preparing (Hf-Zr-Ti-Ta) C ultrahigh-temperature ceramic powder by utilizing a carbon thermal reduction reaction; performing compression molding on the powder to obtain a ceramic block; and finally, sintering the ceramic block body by utilizing pressureless sintering equipment to obtain the (Hf-Zr-Ti-Ta) C quaternary carbide superhigh-temperature ceramic. The pressureless sintering technology which is simple and convenient in process is adopted, so that the production cost is greatly reduced, and the yield is increased; the carbide ceramic block prepared by the preparation method disclosed by the invention has relatively good ablation resistance; technical support is provided for application of the high-temperature anti-ablation carbide ceramic material in hot end components of aerospace vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ultra-high temperature ceramic materials technology, and discloses a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic and its preparation method. Background Technology

[0002] Currently, the global demand for hypersonic vehicles with extended endurance is increasingly urgent, necessitating their operation in harsh environments. Certain critical structural components, such as the nose cone, leading edge, aerodynamic control surfaces, engine combustion chamber, and nozzle, will undergo prolonged ablation tests under extremely high temperatures, pressures, and high-enthalpy chemical non-equilibrium flow. To address these demanding operating environments, it is essential to develop new material systems and explore new thermal protection theories. The performance of thermal protection materials not only determines the speed limit of hypersonic vehicles but also directly affects their service life, serving as a fundamental guarantee for the iterative development of aerospace equipment.

[0003] Ultra-high temperature ceramics, due to their high melting point, high strength, and excellent thermal shock resistance, have become the most commonly used thermal protection materials for aerospace applications. However, single-component thermal protection ceramic materials (ZrB2, HfB2, ZrC, HfC, TaC, HfN, etc.) exhibit rapid oxidation / ablation rates in high-speed, high-temperature, and strong airflow erosion environments, failing to meet current performance requirements for hot-end components of hypersonic vehicles. Therefore, developing new ultra-high temperature materials with superior performance to address the issue of highly stable thermal protection has become paramount for hypersonic vehicle development. Multi-component carbide ultra-high temperature ceramics possess higher hardness and elastic modulus, lower thermal conductivity, and superior oxidation / ablation resistance, promising to solve the problems of insufficient stability and poor oxidation / ablation resistance of traditional carbide ultra-high temperature ceramics during extreme environmental operations, making them an important candidate for thermal protection materials for hot-end components of hypersonic vehicles.

[0004] Reference 1, "Huang B, Chen L, Bai S. Bulk ultrafine binderless WC prepared by spark plasma sintering[J].Scripta Materialia,2006,54(3):441-445," describes the preparation of ultrafine WC powder with a diameter of approximately 200 nm using spark plasma sintering without adding any binder phase. Under a binder-free sintering process at 1773 K for 240 s, the WC was fully densified, exhibiting excellent mechanical properties. However, pressure-assisted sintering equipment such as spark plasma sintering is very expensive and energy-intensive, making it unsuitable for mass production and only suitable for processing small-sized and simple-shaped components.

[0005] Reference 2, "Ren J, Zhang Y, Zhang J, et al. Effects of HfC nanowire amount on the microstructure and ablation resistance of CVD-HfC coating[J]. Ceramics International, 2018, 44(10): 11340-9," describes the preparation of an HfC ceramic coating on the surface of a C / C composite material using chemical vapor deposition (CVD). The coating was applied at an oxyacetylene heat flux density of 2.4 MW / m³. 2 Failure occurred after 120 seconds of continuous ablation. This is because the HfO2 formed by the oxidation of HfC becomes porous and loose after prolonged ablation. During the ablation process, oxygen diffuses through these porous structures into the internal SiC layer and even the C / C matrix, exacerbating the damage to the C / C composite material. Furthermore, the loose framework structure of HfO2 cannot withstand the mechanical erosion during the ablation process, leading to severe cracking and detachment of the oxide layer. Therefore, HfC ceramics exhibit poor ablation resistance.

[0006] Reference 3, "Li B, Li H, Yao X, et al. Preparation and ablation resistance of ZrC nanowires-reinforced CVD-ZrC coating on sharp leading edge C / C composites[J]. Applied Surface Science, 2022, 584," describes the preparation of a ZrC ceramic coating on the surface of C / C composites using chemical vapor deposition at an oxyacetylene heat flux density of 2.4 MW / m³. 2 It fails after continuous ablation for 60 seconds. ZrO2 formed by the oxidation and ablation of ZrC has similar properties to HfO2. After long-term ablation, the ZrO2 oxide layer remains loose and porous, which cannot effectively inhibit oxygen diffusion. Moreover, the loose skeleton structure of ZrO2 cannot resist the mechanical erosion during the ablation process, resulting in severe cracking and detachment of the ZrO2 oxide layer. Therefore, the ablation resistance of ZrC ceramics is also poor.

[0007] In summary, the pressure-assisted sintering method for preparing ceramic bulk materials is costly and energy-intensive, hindering large-scale production. Although HfC and ZrC ceramics possess numerous advantages, such as high melting points (3890℃ and 3540℃), high thermal stability, and low vapor pressure, the ablation resistance of single-component ceramics remains limited. In high-temperature aerobic environments, single HfC ceramics form an HfO2 oxide layer on their surface. Due to the phase transformation of HfO2 under alternating high and low temperatures, the enormous phase transformation stress causes severe damage to the oxide layer. After ablation, single ZrC materials form a loose and porous ZrO2 layer, which is difficult to withstand the erosion of high-speed heat flow. Therefore, when facing more severe ablation environments, single HfC or ZrC ceramics cannot effectively protect the internal structure of the ceramic. In conclusion, it is crucial to develop a cost-effective and simple method for preparing a novel high-performance ultra-high-temperature ceramic. Summary of the Invention

[0008] To address the insufficient ablation resistance of single-component ultra-high temperature ceramics in atmospheres with extremely high speeds and ultra-high temperatures containing oxygen, this invention proposes a high-temperature ablation-resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic and its preparation method by simplifying the sintering process and reducing preparation costs. Using HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, and C powder as raw materials, (Hf-Zr-Ti-Ta)C powder is first prepared using a carbothermal reduction method. Then, this solid solution powder is pressed into sheets and placed in a pressureless sintering furnace to obtain a uniform and dense carbide ceramic block. The (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high temperature ceramic exhibits excellent high-temperature stability and ablation resistance, capable of withstanding ablation by a 3000℃ oxyacetylene flame for 30 seconds with intact structure. This invention provides technical support for the application of multi-component carbide ultra-high temperature ceramics in aerospace hot-end components.

[0009] Specifically, this invention proposes a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic and its preparation method, the preparation method comprising the following steps:

[0010] Step 1: Weigh HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder and C powder, ball mill and mix them, put them into a high-temperature heat treatment furnace with an inert atmosphere for high-temperature heat treatment, and obtain (Hf-Zr-Ta)C solid solution powder through carbothermic reduction reaction.

[0011] Step 2: After thoroughly mixing the obtained (Hf-Zr-Ti-Ta)C solid solution powder with polyvinyl alcohol (PVA) solution, pour the mixture into a mold and press it into shape using a dry press to obtain a carbide ceramic block;

[0012] Step 3: Place the obtained carbide ceramic block in a high-temperature heat treatment furnace for sintering to obtain a dense carbide ceramic block.

[0013] Preferably, the purity of the HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, and C powder is all >99.9%, and the particle size is 1-3μm.

[0014] Preferably, in step 1, the molar ratio of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder and C powder is 1-3:1-3:1-3:0.5-2:20-30.

[0015] Preferably, in step 1, the ball milling is carried out in a polytetrafluoroethylene ball milling jar, the grinding ball material is ZrO2, the ball-to-material ratio is 3:1, and the ball milling is performed at a speed of 200-400 r / min for 6-12 hours.

[0016] Preferably, in step 1, the high-temperature heat treatment includes heating to 1900-2200℃ at a rate of 3-7℃ / min.

[0017] Preferably, in step 1, the holding time for the high-temperature heat treatment is 1.5-2.5 hours, and the furnace is cooled after the high-temperature heat treatment.

[0018] Preferably, in step 2, the concentration of the polyvinyl alcohol (PVA) solution is 0.008-0.028 g / L.

[0019] Preferably, in step 2, the dry press has a load pressure of 20-40 MPa, a loading rate of 20-35 MPa / min, and a holding time of 1-5 min.

[0020] Preferably, in step 3, the sintering includes heating to 1900-2200℃ at a rate of 3-7℃ / min, holding for 1.5-2.5h, and then cooling with the furnace after sintering.

[0021] The high-temperature ablation-resistant (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high-temperature ceramic prepared by this invention has an oxide layer after ablation, the oxide layer including the high-melting-point oxide (Hf,Zr)6Ta2O 17 And (Hf,Zr)O2, as well as low-melting-point oxides Ta2O5 and (Hf,Zr)TiO4.

[0022] Existing sintering processes commonly use spark plasma sintering or hot pressing equipment, which are very expensive and energy-intensive, making them unsuitable for mass production and only suitable for processing small-sized and simple-shaped components. This solution uses pressureless sintering, which allows ceramic blanks of different shapes to be placed in a heat treatment furnace for batch sintering, resulting in high yield, simple operation, and low cost.

[0023] Traditional HfC and ZrC ceramics have high melting points (3890℃ and 3890℃), and their oxides also have high melting points (2810℃ and 2677℃), meaning they can act as a good framework when facing high-temperature flame streams. However, conversely, under high thermal stress, once cracks occur, oxygen rapidly diffuses inward. If the molten phase is not used to fill the cracks and pores, the oxygen erosion on the ceramic surface will be further intensified. The resulting ceramic oxides cannot withstand the erosive effect of the high-speed oxyacetylene flame stream, leading to spalling and triggering a chain reaction that further promotes the diffusion of oxygen-containing streams, thus creating a vicious cycle. Compared to HfC and ZrC ceramics, TiC and TaC ceramics have oxide melting points of only 1840℃ and 1800℃, respectively, which are lower than the actual testing temperature for oxyacetylene. Therefore, this scheme uses the carbothermal reduction method to prepare a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic. An oxyacetylene ablation test was performed on it for 30 seconds. Phase analysis of the oxide layer after ablation was conducted using XRD data. The results show that a high-melting-point oxide (Hf,Zr)6Ta2O was generated during the ablation process. 17 The oxides used in the ablation process included (Hf,Zr)O2 (melting point approximately 2244℃) and (Hf,Zr)O2 (melting point approximately 2715℃), as well as low-melting-point oxides Ta2O5 (melting point approximately 1800℃) and (Hf,Zr)TiO4 (melting point approximately 1840℃). During ablation, the high-melting-point oxides provided support within the oxide layer, while the low-melting-point oxides exhibited good fluidity, effectively reducing defects. This demonstrates a superior synergistic effect between the two oxides with different melting points, resulting in a denser and more stable oxide layer during ablation, thus preventing further oxygen penetration and extending the oxide layer's lifespan. Furthermore, (Hf,Zr)6Ta2O... 17 The particles exhibit a needle-like morphology. Since cracks can be deflected at the interface of these needle-like particles, this morphology effectively prevents cracks caused by thermal expansion and contraction or phase transformation from further extending or propagating, thereby improving the thermal shock resistance of the oxide layer. In summary, this ceramic composition fully utilizes the synergistic effect of multiple components, significantly enhancing its ablation resistance.

[0024] In summary, the present invention has the following advantages:

[0025] 1. This invention combines carbothermal reduction and pressureless sintering to prepare (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high temperature ceramics. Oxyacetylene ablation tests have demonstrated that it has superior ablation resistance, solving the problems of non-dense microstructure, cracking, and spalling of single-unit carbide ultra-high temperature ceramics after ablation.

[0026] 2. The (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high temperature ceramic prepared in this invention exhibits excellent ablation resistance after oxyacetylene ablation, with a dense surface, low ablation temperature, and good synergistic effect between phases. This lays a theoretical foundation for subsequent research on the ablation resistance of medium / high entropy carbide ceramics. Attached Figure Description

[0027] Figure 1 This is the XRD pattern of the (Hf-Zr-Ti-Ta)C ceramic block before ablation in Example 1 of this invention;

[0028] Figure 2 This is the XRD pattern of the (Hf-Zr-Ti)C ceramic block before ablation in Comparative Example 1 of this invention;

[0029] Figure 3 This is the XRD pattern of the (Hf-Zr-Ta)C ceramic block before ablation in Comparative Example 2 of this invention;

[0030] Figure 4 These are the microstructure and EDS analysis images of the (Hf-Zr-Ti-Ta)C ceramic before ablation in Example 1 of this invention;

[0031] Figure 5 These are the microstructure and EDS analysis images of the ((Hf-Zr-Ti)C ceramic before ablation in Comparative Example 1 of this invention;

[0032] Figure 6 These are the microstructure and EDS analysis images of the (Hf-Zr-Ta)C ceramic before ablation in Comparative Example 2 of this invention;

[0033] Figure 7 This is the XRD pattern of the (Hf-Zr-Ti-Ta)C ceramic block after ablation in Example 1 of this invention;

[0034] Figure 8 This is the XRD pattern of the (Hf-Zr-Ti)C ceramic block after ablation in Comparative Example 1 of this invention;

[0035] Figure 9 This is the XRD pattern of the (Hf-Zr-Ta)C ceramic block after ablation in Comparative Example 2 of this invention;

[0036] Figure 10 These are the microstructure and EDS analysis images of the (Hf-Zr-Ti-Ta)C ceramic after ablation in Example 1 of this invention;

[0037] Figure 11 These are the microstructure and EDS analysis images of the (Hf-Zr-Ti)C ceramic after ablation in Comparative Example 1 of this invention;

[0038] Figure 12The following are the microstructure and EDS analysis images of the (Hf-Zr-Ta)C ceramic after ablation in Comparative Example 2 of this invention: (a) SEM image of the ablated surface; (b) magnified view of (a); (c) elemental distribution map corresponding to (b);

[0039] Figure 13 This is a comparison of the macroscopic morphology of Embodiment 1 of the present invention with that of Comparative Examples 1 and 2 after ablation;

[0040] Figure 14 This is a comparison of the highest ablation temperature and ablation rate of the ablation surface of Example 1 of the present invention with those of Comparative Examples 1 and 2. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0042] Example 1

[0043] A method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic includes the following steps:

[0044] Step 1: Weigh HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder and C powder in a molar ratio of 2:2:2:1:25. Pour the weighed powder into a polytetrafluoroethylene ball mill jar with a ball-to-powder ratio of 3:1. Add industrial alcohol and wet mill for 8 hours. Then dry in a constant temperature drying oven at 70°C for 10 hours. This step will yield a uniform oxide mixed powder. The oxide mixture powder was poured into a graphite crucible with graphite paper lining the inner wall, and then placed in a high-temperature heat treatment furnace protected by Ar gas. The heating rate was 5℃ / min, and the temperature was raised to 2100℃ and held for 2 hours, followed by natural cooling with the furnace. The carbothermic reduction reaction yielded (Hf-Zr-Ti-Ta)C solid solution bulk material, which was placed in a polytetrafluoroethylene ball mill jar with a ball-to-material ratio of 3:1. Industrial alcohol was added and the mixture was wet-milled for 8 hours. The mixture was then placed in a constant temperature drying oven at 70℃ and dried for 10 hours. This step yielded (Hf-Zr-Ti-Ta)C ceramic powder.

[0045] Step 2: Take 5g of the (Hf-Zr-Ti-Ta)C ceramic powder obtained in Step 1 and place it in an agate mortar. Add 3 drops of PVA solution using a dropper, grind for 10 minutes, and then pour in Cr... 12In the MoV mold, the mold is placed under the pressure head of a dry press, the load pressure is set to 30MPa, and the pressure is held for 1.5 minutes before being unloaded. After this step, a preliminary (Hf-Zr-Ti-Ta)C ceramic preform can be obtained.

[0046] Step 3: Wrap the (Hf-Zr-Ti-Ta)C ceramic blank obtained in Step 2 with graphite paper, place it in a graphite crucible with graphite paper lining the inner wall, and then place it in a high-temperature heat treatment furnace protected by Ar gas. The heating rate is 5℃ / min. After heating to 2100℃, hold for 2 hours, and then let it cool naturally in the furnace. This step yields a sintered and dense (Hf-Zr-Ti-Ta)C ceramic block.

[0047] Figure 1 This is the XRD pattern of the (Hf-Zr-Ti-Ta)C ceramic bulk before ablation, from... Figure 1 It can be seen that (Hf-Zr-Ti-Ta)C ceramics are prepared by carbothermal reduction reaction. Figure 4 The image shows the microstructure and EDS analysis of (Hf-Zr-Ti-Ta)C ceramic before ablation. As can be seen from the image, no obvious aggregation or segregation of the elements (Hf, Zr, Ti, Ta) was observed, indicating that the elements in (Hf-Zr-Ti-Ta)C ceramic are uniformly distributed.

[0048] The prepared (Hf-Zr-Ti-Ta)C ceramic bulk was subjected to oxyacetylene ablation testing. The oxyacetylene flame heat flux density was 2.4 MW / m³. 2 The acetylene gas flow rate was 0.18 L / s, the oxygen gas flow rate was 0.24 L / s, the acetylene pressure was 0.095 MPa, the oxygen pressure was 0.4 MPa, and the ablation time was 30 s. After 30 s of ablation, no obvious defects were observed on the upper surface of the ceramic block, except for a color change.

[0049] Figure 7 This is the XRD pattern of a (Hf-Zr-Ti-Ta)C ceramic bulk after ablation for 30 s. The figure shows that the oxide layer after ablation mainly consists of high-melting-point oxides (Hf,Zr)O2 and (Hf,Zr)6Ta2O. 17 It consists of low-melting-point oxides Ta2O5 and (Hf,Zr)TiO4. Figure 10 These are the microstructure and EDS analysis images of (Hf-Zr-Ti-Ta)C ceramic after ablation for 30 s. The microstructure images show that the oxide layer surface after ablation is relatively dense, effectively preventing further oxygen penetration and exhibiting good ablation resistance. EDS data analysis reveals that during the ablation process, the oxide layer surface contains the high-melting-point oxide (Hf,Zr)6Ta2O. 17The needle-shaped particles are embedded in the low-melting-point oxides, providing support. The Ti-dominant low-melting-point molten phase oxide (Hf,Zr)TiO4 effectively fills defects, significantly improving the adhesion and density of the oxide layer and effectively inhibiting large-scale peeling under oxyacetylene flame erosion. Simultaneously, cracks generated during ablation due to thermal expansion and contraction or phase transformation can be deflected at the interface of the needle-shaped particles, thus inhibiting crack propagation and improving the thermal shock resistance of the oxide layer. Furthermore, the abundant low-melting-point oxides Ta2O5 and (Hf,Zr)TiO4 carry away heat during melting and volatilization, lowering the surface temperature of the ceramic during ablation and reducing thermal stress concentration. In summary, (Hf-Zr-Ti-Ta)C ceramics fully utilize the synergistic effect between its multiple components during ablation, greatly enhancing its ablation resistance.

[0050] Comparative Example 1

[0051] This example is prepared according to the following steps:

[0052] Step 1: Weigh HfO2 powder, ZrO2 powder, TiO2 powder, and C powder in a molar ratio of 1:1:1:9. Pour the weighed powder into a polytetrafluoroethylene ball mill jar with a ball-to-powder ratio of 3:1. Add industrial alcohol and wet mill for 8 hours. Then, dry in a constant temperature drying oven at 70℃ for 10 hours. This step yields a uniform oxide mixture powder. Pour the oxide mixture powder into a graphite crucible with the inner wall lined with graphite paper. Then, place it in a high-temperature heat treatment furnace under Ar gas protection. The heating rate is 5℃ / min. After heating to 2100℃, hold at that temperature for 2 hours, and then allow it to cool naturally in the furnace. (Hf-Zr-Ti)C solid solution bulk material was prepared by carbothermal reduction reaction, placed in a polytetrafluoroethylene ball mill jar with a ball-to-material ratio of 3:1, wet-milled with industrial alcohol for 8 hours, and then dried in a constant temperature drying oven at 70℃ for 10 hours. After this step, (Hf-Zr-Ti)C ceramic powder can be obtained.

[0053] Step 2: Take 5g of the (Hf-Zr-Ti)C ceramic powder obtained in Step 1 and place it in an agate mortar. Add 3 drops of PVA solution using a dropper, grind for 10 minutes, and then pour in Cr... 12 In the MoV mold, the mold is placed under the pressure head of a dry press, the load pressure is set to 30MPa, and the pressure is held for 1.5 minutes before unloading. After this step, a preliminary (Hf-Zr-Ti)C ceramic preform can be obtained.

[0054] Step 3: Wrap the (Hf-Zr-Ti)C ceramic blank obtained in Step 2 with graphite paper, place it in a graphite crucible with graphite paper lining the inner wall, and then place it in a high-temperature heat treatment furnace protected by Ar gas. The heating rate is 5℃ / min. After heating to 2100℃, hold for 2 hours, and then let it cool naturally in the furnace. This step yields a sintered and dense (Hf-Zr-Ti)C ceramic block.

[0055] Figure 2 This is the XRD pattern of the (Hf-Zr-Ti)C ceramic bulk before ablation, from... Figure 2 It can be seen that (Hf-Zr-Ti)C ceramics are prepared by carbothermic reduction reaction. Figure 5 The images show the microstructure and EDS analysis of (Hf-Zr-Ti)C ceramic before ablation. As can be seen from the images, no obvious aggregation or segregation of the elements (Hf, Zr, Ti) was observed, indicating that the elements in (Hf-Zr-Ti)C ceramic are uniformly distributed.

[0056] The prepared (Hf-Zr-Ti)C ceramic bulk was subjected to oxyacetylene ablation testing. The oxyacetylene heat flux density was 2.4 MW / m³. 2 The acetylene gas flow rate was 0.18 L / s, the oxygen gas flow rate was 0.24 L / s, the acetylene pressure was 0.095 MPa, the oxygen pressure was 0.4 MPa, and the ablation time was 30 s. The (Hf-Zr-Ti)C ceramic block prepared by combining carbothermal reduction and pressureless sintering showed multiple cracks on its macroscopic surface after 30 s of ablation, indicating poor resistance to oxygen erosion.

[0057] Figure 8 The image shows the XRD pattern of (Hf-Zr-Ti)C ceramic bulk after ablation for 30 s. As can be seen from the image, the oxide layer after ablation is mainly composed of high-melting-point oxide (Hf,Zr)O2, and low-melting-point oxides (Hf,Zr,Ti)O2 and (Hf,Zr)TiO4.

[0058] Figure 11 These are the microstructure and EDS analysis images of (Hf-Zr-Ti)C ceramic after ablation for 30 seconds. The microstructure images show numerous cracks and pores on the oxide layer surface after ablation, providing rapid pathways for oxygen intrusion. EDS data analysis reveals that the oxide layer surface is mainly composed of high-melting-point oxides (Hf,Zr)O2. This is because Ti-rich low-melting-point oxides are easily volatilized and quickly eroded and volatilized under high-temperature heat flow, forming numerous pores. Meanwhile, the high-melting-point oxides (Hf,Zr)O2, due to their high melting point and relative stability at high temperatures, are retained, forming a sparse and porous "skeleton" structure. This structure, under prolonged high-temperature airflow, leads to cracking and peeling of the oxide layer.

[0059] Comparative Example 2

[0060] This example is prepared according to the following steps:

[0061] Step 1: Weigh HfO2 powder, ZrO2 powder, Ta2O5 powder, and C powder in a molar ratio of 2:2:1:19. Pour the weighed powder into a polytetrafluoroethylene ball mill jar with a ball-to-powder ratio of 3:1. Add industrial alcohol and wet mill for 8 hours. Then, dry in a constant temperature drying oven at 70℃ for 10 hours. This step yields a uniform oxide mixture powder. Pour the oxide mixture powder into a graphite crucible with the inner wall lined with graphite paper. Then, place it in a high-temperature heat treatment furnace under Ar gas protection. The heating rate is 5℃ / min. After heating to 2100℃, hold at that temperature for 2 hours, and then allow it to cool naturally in the furnace. (Hf-Zr-Ta)C solid solution bulk material was prepared by carbothermal reduction reaction, placed in a polytetrafluoroethylene ball mill jar with a ball-to-material ratio of 3:1, wet-milled with industrial alcohol for 8 hours, and then dried in a constant temperature drying oven at 70℃ for 10 hours. After this step, (Hf-Zr-Ta)C ceramic powder can be obtained.

[0062] Step 2: Take 5g of the (Hf-Zr-Ta)C ceramic powder obtained in Step 1 and place it in an agate mortar. Add 3 drops of PVA solution using a dropper, grind for 10 minutes, and then pour in Cr... 12 In the MoV mold, the mold is placed under the pressure head of a dry press, the load pressure is set to 30MPa, and the pressure is held for 1.5 minutes before unloading. After this step, a preliminary (Hf-Zr-Ta)C ceramic preform can be obtained.

[0063] Step 3: Wrap the (Hf-Zr-Ta)C ceramic blank obtained in Step 2 with graphite paper, place it in a graphite crucible with graphite paper lining the inner wall, and then place it in a high-temperature heat treatment furnace protected by Ar gas. The heating rate is 5℃ / min. After heating to 2100℃, hold for 2 hours, and then let it cool naturally in the furnace. This step yields a sintered and dense (Hf-Zr-Ta)C ceramic block.

[0064] Figure 3 This is the XRD pattern of the (Hf-Zr-Ta)C ceramic bulk before ablation, from... Figure 3 It can be seen that (Hf-Zr-Ta)C ceramics are prepared by carbothermic reduction reaction. Figure 6 The image shows the microstructure and EDS analysis of (Hf-Zr-Ta)C ceramic before ablation. As can be seen from the image, no obvious aggregation or segregation of the elements (Hf, Zr, Ta) was observed, indicating that the elements in (Hf-Zr-Ta)C ceramic are uniformly distributed.

[0065] The prepared (Hf-Zr-Ta)C ceramic bulk was subjected to oxyacetylene ablation testing. The oxyacetylene heat flux density was 2.4 MW / m³. 2The acetylene gas flow rate was 0.18 L / s, the oxygen gas flow rate was 0.24 L / s, the acetylene pressure was 0.095 MPa, the oxygen pressure was 0.4 MPa, and the ablation time was 30 s. The (Hf-Zr-Ta)C ceramic blocks prepared by combining carbothermal reduction and pressureless sintering showed some cracks and protrusions on the macroscopic surface after ablation, with partial peeling of the oxide layer at the edges and depressions appearing in the ablation center.

[0066] Figure 9 This is the XRD pattern of (Hf-Zr-Ta)C ceramic bulk after ablation. The figure shows that the oxide layer after ablation is mainly composed of the high-melting-point oxide Hf6Ta2O. 17 TaZr 2.75 It is composed of O8 and (Hf,Zr)O2, as well as the low-melting-point oxide Ta2O5.

[0067] Figure 12 These are the microstructure and EDS analysis images of (Hf-Zr-Ta)C ceramic after ablation. The microstructure images show numerous ablation pits and protrusions on the oxide layer surface after ablation, indicating poor resistance to ablation and erosion. EDS data analysis reveals that these protrusions are composed of high-melting-point oxides. This suggests that during the high-temperature ablation process, a large amount of low-melting-point oxides melted into liquid and were quickly eroded and volatilized under the high-temperature heat flow, forming numerous pores and pits. Meanwhile, the high-melting-point oxides, due to their high melting point and stability at high temperatures, were retained, forming the protrusions on the oxide layer surface.

[0068] Figure 13 This is a comparison of the macroscopic morphology of Embodiment 1 of the present invention with Comparative Examples 1 and 2 after ablation; according to Figure 13 As can be seen, the oxide layer of (Hf-Zr-Ti-Ta)C in Example 1 remained "intact and dense" after ablation, with no cracks or peeling on the surface; the morphology diagram showed that the material structure was intact and there was no obvious damage. The oxide layer of (Hf-Zr-Ti)C in Comparative Example 1 was "severely cracked," indicating that the material had poor thermal shock resistance and could not withstand ablation stress; the oxide layer of (Hf-Zr-Ta)C in Comparative Example 2 showed a large number of protrusions on the surface and peeling at the edges, reflecting local deformation and delamination failure of the material at high temperature.

[0069] Figure 14 This is a comparison of the highest ablation temperature and ablation rate of the ablation surface in Embodiment 1 of the present invention with Comparative Examples 1 and 2. According to... Figure 14 It can be seen that the (Hf-Zr-Ti-Ta)C in Example 1 has the lowest maximum temperature on the ablation surface, and has a more efficient heat radiation / heat dissipation capability, thus slowing down the accumulation of high temperature.

[0070] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention; the actual structure is not limited thereto. In conclusion, if those skilled in the art are inspired by this description and design similar structures and embodiments without departing from the spirit of the invention, such designs should fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic, characterized in that, Includes the following steps: Step 1: Weigh HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder and C powder, ball mill and mix them, put them into a high-temperature heat treatment furnace with an inert atmosphere for high-temperature heat treatment, and obtain (Hf-Zr-Ti-Ta)C solid solution powder through carbothermic reduction reaction. Step 2: After thoroughly mixing the (Hf-Zr-Ti-Ta)C solid solution powder obtained in Step 1 with the polyvinyl alcohol (PVA) solution, pour the mixture into a mold and press it into shape using a dry press to obtain a carbide ceramic block. Step 3: Place the carbide ceramic block obtained in Step 2 into a high-temperature heat treatment furnace for sintering to obtain a dense carbide ceramic block.

2. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 1, characterized in that: In step 1, the purity of the HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, and C powder is all >99.9%, and the particle size is 1-3μm.

3. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 2, characterized in that: The molar ratio of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder and C powder is 1-3:1-3:1-3:0.5-2:20-30.

4. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 3, characterized in that: In step 1, the ball milling is carried out in a polytetrafluoroethylene ball milling jar, the grinding ball material is ZrO2, the ball-to-material ratio is 3:1, and the ball milling is performed at a speed of 200-400 r / min for 6-12 hours.

5. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 1, characterized in that: In step 1, the high-temperature heat treatment includes heating to 1900-2200℃ at a rate of 3-7℃ / min.

6. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 5, characterized in that: In step 1, the holding time for the high-temperature heat treatment is 1.5-2.5 hours, and the furnace is cooled after the high-temperature heat treatment.

7. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 1, characterized in that: In step 2, the concentration of the polyvinyl alcohol (PVA) solution is 0.008-0.028 g / L.

8. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 7, characterized in that: In step 2, the dry press has a load pressure of 20-40 MPa, a loading rate of 20-35 MPa / min, and a holding time of 1-5 min.

9. The method for preparing a high-temperature resistant (Hf-Zr-Ti-Ta)C carbide ultra-high temperature ceramic according to claim 1, characterized in that: In step 3, the sintering includes heating to 1900-2200℃ at a rate of 3-7℃ / min, holding for a preferred time of 1.5-2.5h, and then cooling with the furnace after sintering.

10. A high-temperature ablation-resistant (Hf-Zr-Ti-Ta)C quaternary carbide ultra-high-temperature ceramic prepared by the preparation method according to any one of claims 1-9, characterized in that: The ceramic is ablated to obtain an oxide layer, which includes a high-melting-point oxide (Hf,Zr)6Ta2O. 17 And (Hf,Zr)O2, as well as low-melting-point oxides Ta2O5 and (Hf,Zr)TiO4.